Aftermath deportation law and the new American diaspora - Kanstroom, Dan. (New York ; Oxford : Oxford University Press, 2012)
Addressing various political, social, philosophical and legal issues, Kanstroom considers how deportation works within the 'rule of law'. He recounts stories of immigrants to highlight what actually happens to them after they are deported. After concluding that the U.S. deportation system remains an anachronistic, ad hoc, legally dubious affair, the book offers specific proposals for a more humane and rational deportation system.
Description based on online resource; title from PDF title page (viewed on July 5, 2012).
Includes bibliographical references and index.
Keywords: Deportation -- United States; Emigration and immigration law -- United States; Rule of law -- United States; Deportees -- United States